THE EPIDEMIOLOGICAL OVERVIEW OF ACUTE FLACCID PARALYSIS CASES IN SURABAYA DURING 2014-2017 - Dwiki Noni Armyta (Jurnal Berkala Epidemiologi, 2019)
Background: During 2017 to 2018, 168 polio cases were found globally that caused an increase of awareness towards the emergence of poliovirus in Indonesia. AFP surveillance was the primary strategy to overcome global polio. Therefore, the understanding of the epidemiological characteristics becomes very important to improve the success of AFP surveillance systems. Purpose: This study aims to describe the epidemiological characteristics and types of diagnosis of AFP cases in Surabaya from 2014 to 2017. Method: This study was a descriptive study with a case series design. Data sources utilized was secondary data from AFP surveillance report of Surabaya City Health Office from 2014 to 2017. Results: Total AFP cases in Surabaya from 2014 to 2017 recorded 54 cases with annual AFP Non-Polio Incidence rate of approximately 3.85/100,000 children aged <15 years old in 2017. The result of the final diagnosis was Guillain Barre Syndrome (GBS) (44.44%). AFP mostly affected children in the age of group 1-4 years old (42.59%). Most AFP cases occurred in men (74.07%) and were more commonly found in areas with a high population density. The increasing case pattern occurred in October in the last two years. Conclusion: The AFP Non-Polio case finding in Surabaya was classified high with the highest case pattern during 2014-2017. The incidents occurred in male at the age group 1-4 years old, and Guillain Barre Syndrome became the most common case diagnosis.